Integrated transcriptome and metabolome profiling reveals mechanisms underlying the infection of Cytospora mali in “Jin Hong” branches - Zhao, Jing; Guo, Yuan; Li, Zhengnan; Shi, Yajun; Sun, Pingping (Frontiers in Microbiology, 2024)
Valsa canker, caused by Cytospora mali, is a destructive disease in apple production. However, the mechanism by which apple defend against C. mali infection remains unclear. In this study, the integrative transcriptional and metabolic analysis were used to we investigated the transcriptional and metabolic the responses of the 'Jin Hong' apple branches after to the invasion of C. mali. The results Results showed that C. mali infection significantly altered the transcriptional and metabolic profiles of the apple. The study found that the differentially expressed genes were mainly enriched in the pathways of carbon metabolism, photosynthesis-antenna proteins, and biosynthesis of amino acids pathways. Additionally, the differentially accumulated metabolites were significantly enriched in aminoacyl-tRNA biosynthesis, fructose and mannose metabolism, and alanine, aspartate, and glutamate metabolism pathways. Conjoint analysis revealed that C. mali infection significantly altered 5 metabolic pathways, 8 highly relevant metabolites and 15 genes of apples. Among whichFurthermore, in the case of C. mali attack, the transcription factors WRKY and basic domain leucine zipper transcription family were induced. There was significant up-and down-regulation of metabolites such as, the α-linolenic acid and chlorogenic acidbetaine were significantly accumulated in C. mali infected apple stems. This work presents an overview of the changes in gene expression and metabolic profiles in apple under the stress inoculation of C. mali, which may help to further screen out the mechanism of plant-pathogen interaction at the molecular level.